Warm-season precipitation drivers in northeastern Argentina: Diurnal cycle of the atmospheric moisture balance and land–atmosphere coupling - Giles, Julián Alberto (2020)
Southeastern South America is influenced by moisture transport from lower latitudes, sustainsintense convective storms and is a land-atmosphere coupling hotspot, but the interconnectionbetween these processes is still not well understood. We present the warm-season diurnal cycleclimatology of the water balance components in the South American Low-Level Jet (SALLJ) exitregion in northeastern Argentina during 1998-2012. Different precipitation-based types of events(clear-sky and rainy days) were explored together with processes tied to the land-atmospherecoupling at the daily scale. Our research was based on simulations with and without soilmoisture-atmosphere coupling with the RCA4 regional climate model. A control simulation wascompared with a sensitivity simulation where the soil moisture was prescribed with the dailyclimatological values from the control run. The ERA5 reanalysis and the satellite precipitationproducts TRMM-3B42 v7 and CMORPH v1.0 bias corrected were used for comparativepurposes. From the diurnal water balance analysis we found that moisture flux convergence inthe region is the main driver for nocturnal precipitation while local evapotranspiration feedsafternoon rain events. Rainy afternoons do not show differences between simulations, but rainynights seem to be affected. Moreover, daily correlations between surface and boundary-layervariables showed that the local coupling is weaker during rainy days than during clear-sky days.Therefore, we suggest that changes in non-local drivers, such as the moisture flux through theSALLJ, are more relevant for rainy nights than the local coupling.